Hypoglycemic Hypolipidemic Evaluation of a Polyherbal Phytocomposite and the Mechanism of its Synergistic Anti-Diabetic Effect - De, Baishakhi (International Journal of Pharmaceutical & Biological Archive, 2017)
This research aims to study the safety profile of a Polyherbal phytocomposite (PHC) prepared from the leaf powders of Ficus benghalensis (Banyan), Syzigium cumini (Jamun) and Ocimum sanctum (Tulsi) followed by its in vivo hypoglycemic and hypolipidemic studies and comparative evaluation of its effect with its constituent species. PHC did not show any adversities like mortality signs or behavioral anomalies at doses of 7.5g/kg body weight; first death was recorded at 10g/kg. PHC increased body weight to some extent with significant (p<0.05) changes in organ weight at doses of 500 and 750mg/kg. There was a significant decrease in plasma protein, ALT and increase in creatinine, AST at p<0.05 level at a dose of 750mg/kg. The hemoglobin levels were also significantly increased. PHC showed significant lowering of fasting blood glucose and blood lipid (p<0.001) with actions better than metformin. The hypoglycemic-hypolipidemic action of the PHC when compared with its constituent plant species (Banyan, Jamun and Tulsi) and standard drug metformin was found to be significantly better (p<0.001) thus suggesting phytosynergism amongst the phytomolecules present within PHC.